Throw and Catch: Analyzing the Synchronized Movements of Eyes and Joints in Children - Ziyu He; Hong Fu; Ruimin Li; Zhen Liang; Chetwyn C. H. Chan; Yanwen Xu; Yang Zheng (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2025)
Throw and catch are fundamental motor skills that are closely related to eye-hand coordination, reaction speed, and spatial awareness in children. Current research on throw and catch mainly focuses on the impact of attentional focus, anticipatory knowledge, and training on visuomotor control. Little work has been done on the synchronized movements of eyes and joints during the throw and catch. To understand how these synchronized movements contribute to the success rate of throwing and catching, we proposed a video-based framework named Synchronized Eye and Joint Analysis (SEJA). This framework locates, extracts, and analyzes the essential eye and joint movements from untrimmed first-person and third-person view videos. Using the proposed framework, throw and catch events in long untrimmed videos were successfully identified, and whether each catch was successful was accurately assessed. Additionally, detailed metrics related to predictive gaze behaviors and predictive hand movements for each catch event were obtained. On a dataset consisting of videos from 56 children aged 7 to 10, the proposed framework delivered an average precision (AP) ranging from 0.5 to 0.95 at 0.881 for task localization and achieved an accuracy of 0.985 in predicting whether a catch was successful. Our research indicated that children with higher catch success rates showed shorter delays in predicting the ball’s trajectory, smaller amplitudes of body movement, and more pronounced predictive saccades (rapid eye movements to anticipate the ball’s position). These findings are crucial for comprehending and improving the development of motor skills in children.